Dose differences between the three dose calculation algorithms in Leksell GammaPlan. (8th September 2014) - Xu, Andy (Yuanguang); Bhatnagar, Jagdish; Bednarz, Greg; Niranjan, Ajay; Flickinger, John; Lunsford, L. Dade; Huq, M. Saiful
Abstract : The purpose of this study was to evaluate the dose differences introduced by the TMR 10 and the convolution dose calculation algorithms in GammaPlan version 10, as compared to the TMR classic algorithm in the previous versions of GammaPlan. Computed axial tomographic images of a polystyrene phantom and a human head were acquired using a GE LightSpeed VCT scanner. A treatment target with a prescription dose of 20 Gy to 50% isodose line was defined in the phantom or the head CT set. The treatment times for single collimator, single shot placements were calculated using the three dose calculation algorithms in GammaPlan version 10. Four comparative studies were conducted: i) the dose matrix position was varied every 10 mm along the x‐, y‐, z‐axes of the stereotactic coordinate system inside the phantom and the treatment times were compared on each matrix for the three collimators of the Gamma Knife Perfexion and the four collimators of the 4C; ii) the study was repeated for the human head CT dataset; iii) the matrix position was varied every 20 mm in the X and the Y directions on the central slice ( Z   =   100   mm ) of the head CT and the shot times were compared on each matrix for the 8 mm collimator of both units; a total of 51 matrix positions were identified for each unit; iv) the above comparison was repeated for the head CT transverse slices with Z   =   20,   40,   60,   80,   120,   140, and 160 mm. A total of 271 matrix positions were studied. Based on the comparison of the treatment times needed to deliver 20 Gy at 50% isodose line, the equivalent TMR classic dose of the TMR 10 algorithm is roughly a constant for each collimator of the 4C unit and is 97.5%, 98.5%, 98%, and 100% of the TMR 10 dose for the 18 mm, 14 mm, 8 mm, and the 4 mm collimators, respectively. The numbers for the three collimators of the Perfexion change with the shot positions in the range from 99% to 102% for both the phantom and the head CT. The minimum, maximum, and the mean values of the equivalent TMR classic doses of the convolution algorithm on the 271 voxels of the head CT are 99.5%, 111.5%, 106.5% of the convolution dose for the Perfexion, and 99%, 109%, 104.5% for the 4C unit. We identified a maximum decrease in delivered dose of 11.5% for treatment in the superior frontal/parietal vertex region of the head CT for older calculations lacking inhomogeneity correction to account for the greater percentage of the average beam path occupied by bone. The differences in the inferior temporal lobe and the cerebellum/neck regions are significantly less, owing to the counter‐balancing effects of both bone and the air cavity inhomogeneities. The dose differences between the TMR 10 and the TMR classic are within ±   2.5 % for a single shot placement on both Perfexion and 4C. Dose prescriptions based on the experiences with the TMR classic may need to be adjusted to accommodate the up to 11.5% difference between the convolution and the TMR classic. PACS numbers: 87.55.D, 87.55.kd